2017
DOI: 10.1007/s13770-016-0020-3
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Exposure to Myrtucommulone-A Changes CD105 Expression and Differentiation Potential of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) represent a heterogeneous group of multipotent stem cells that could be found in various somatic tissues. MSCs are defined by molecular and functional features including spindle-shape morphology, adherence to plastic surfaces, expression of specific surface markers and differentiation potential to chondrocytes, adipocytes and osteocytes. The surface markers were proposed to affect the differentiation potential of MSCs by a limited number of studies. Endoglin (CD105) is defined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Jiang et al found that CD105(+) ADSC subpopulation in in vitro culture had a much stronger chondrogenic potential than CD105(−) subpopulation and had more intensive immunostaining of type II collagen and higher gene expression of COL2A1 and ACAN following chondrogenic induction 40 . There is also a report that myrtucommulone-A treatment reduced CD105 expression in expanded human ADSCs along with reduced chondrogenic potential 41 .…”
Section: Cd105mentioning
confidence: 99%
“…Jiang et al found that CD105(+) ADSC subpopulation in in vitro culture had a much stronger chondrogenic potential than CD105(−) subpopulation and had more intensive immunostaining of type II collagen and higher gene expression of COL2A1 and ACAN following chondrogenic induction 40 . There is also a report that myrtucommulone-A treatment reduced CD105 expression in expanded human ADSCs along with reduced chondrogenic potential 41 .…”
Section: Cd105mentioning
confidence: 99%
“…The lower quality of cartilage-like tissue produced by iMSC#6 and iMSC#9 in comparison with T-MSC#6 could be suggested as a result of its lower CD105 positivity, as it is part of the TGF-ß receptor complex. However, it has been noted that CD105 + MSCs have no superior chondrogenic potential than the CD105ones [68], even though it is still controversial [69]. It has also been stated that, as a counterpart of decreased chondrogenic potential, CD105 -MSCs show increased osteogenic potential [69] as a result of superior adhesion and mineralization efficiency [70], which might be related to the superior osteogenic potential of iMSCs.…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…However, it has been noted that CD105 + MSCs have no superior chondrogenic potential than the CD105ones [68], even though it is still controversial [69]. It has also been stated that, as a counterpart of decreased chondrogenic potential, CD105 -MSCs show increased osteogenic potential [69] as a result of superior adhesion and mineralization efficiency [70], which might be related to the superior osteogenic potential of iMSCs. Nevertheless, surface marker expression does not necessarily reflect the functional capacities of MSC [63], and the inferior osteogenic potential of primary MSC#6 may be also due to them being differentiated at the 6th passage, when cells are expected to be aged [5,71].…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…Treatment with this product reduced the chondrogenic potential in human mesenchymal stem cell (hMSC) lines, possibly as a consequence of the NF-κB p65 activation, while the adipogenic or osteogenic differentiation was not dramatically affected. The exploitation of these properties could be useful in targeted differentiation studies [113].…”
Section: Biological Activitiesmentioning
confidence: 99%